2015
DOI: 10.1016/j.chemosphere.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of polycyclic aromatic hydrocarbons exposure in small groups of residents in Brisbane, Australia and Hanoi, Vietnam, and those travelling between the two cities

Abstract: Exposure to polycyclic aromatic hydrocarbons (PAHs) has been associated with adverse health outcomes. Concentrations of urinary PAH metabolites (OH-PAHs) provide an integrated measure of human exposure to PAHs but measurement of urinary OH-PAHs has not been done in Australia and rarely in Vietnam, where air pollution is of concern. In this study, we assessed exposure to PAHs in 16 participants living in Brisbane, Australia and Hanoi, Vietnam, with 4 participants travelling between the two cities during the mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…1-Pyr is a commonly used urinary biomarker of PAHs exposure. The urinary concentrations of 1-Pyr measured in this study (median: 0.38 ng/mL; 0.28 μg/g creatinine) were comparable to those reported from Poland (median: 0.36 μg/g creatinine) ( Sochacka-Tatara et al 2018 ), but higher than those reported from the United States (mean/median: 0.11–0.13 ng/mL) ( CDC 2019 ), Canada (mean/median: 0.09–0.11 ng/mL) ( Health Canada 2017 ), Czech Republic (median: 0.18 μg/g creatinine) ( Urbancova et al 2017 ), and Australia (0.06–0.14 ng/mL) ( Thai et al 2020 ; Thai et al 2015 ), and an order of magnitude lower than those reported from China (mean/median: 3.1–6.4 μg/g creatinine) ( Cao et al 2020a ; Li et al 2015a ).…”
Section: Resultsmentioning
confidence: 66%
“…1-Pyr is a commonly used urinary biomarker of PAHs exposure. The urinary concentrations of 1-Pyr measured in this study (median: 0.38 ng/mL; 0.28 μg/g creatinine) were comparable to those reported from Poland (median: 0.36 μg/g creatinine) ( Sochacka-Tatara et al 2018 ), but higher than those reported from the United States (mean/median: 0.11–0.13 ng/mL) ( CDC 2019 ), Canada (mean/median: 0.09–0.11 ng/mL) ( Health Canada 2017 ), Czech Republic (median: 0.18 μg/g creatinine) ( Urbancova et al 2017 ), and Australia (0.06–0.14 ng/mL) ( Thai et al 2020 ; Thai et al 2015 ), and an order of magnitude lower than those reported from China (mean/median: 3.1–6.4 μg/g creatinine) ( Cao et al 2020a ; Li et al 2015a ).…”
Section: Resultsmentioning
confidence: 66%
“…As toxic air pollutants, PAHs were also present in higher concentrations in Beijing than in other cities in the developed countries. In 2012, the University of California, Los Angeles (UCLA) and Peking University (PKU) carried out a summer exchange program in which a panel of 10 UCLA students traveled to Beijing and stayed for 10 weeks, providing an opportunity to study their PAH exposures and related lipid peroxidation. As shown in a previous study, repeated measurements on travelers could allow researchers to focus on the impacts of exposure with less interference from individual differences . In this study, the first-morning urine samples of these students were collected before, during, and after the exchange program.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in a previous study, repeated measurements on travelers could allow researchers to focus on the impacts of exposure with less interference from individual differences. 21 In this study, the first-morning urine samples of these students were collected before, during, and after the exchange program. A total of 12 urinary OH-PAHs and malondialdehyde (MDA) were measured as surrogates for exposure and lipid peroxidation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example, US National Health and Nutrition Examination Survey (NHANES) data (2001–2006) for OH-PAHs have been used to investigate associations between exposure to PAHs and childhood obesity (Scinicariello and Buser, 2014). Although there have been some biomonitoring studies conducted in the general Australian population for other chemicals, including polyfluorinated alkyl substances and brominated flame retardants (Toms et al, 2014; Toms et al, 2012), to our knowledge there are no data on PAH exposure except for a small group of nine people (Thai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%